Pauls Online Notes
Pauls Online Notes
Home / Calculus I / Derivatives / Derivatives of Trig Functions
Show Mobile Notice Show All Notes Hide All Notes
Mobile Notice
You appear to be on a device with a "narrow" screen width (i.e. you are probably on a mobile phone). Due to the nature of the mathematics on this site it is best views in landscape mode. If your device is not in landscape mode many of the equations will run off the side of your device (should be able to scroll to see them) and some of the menu items will be cut off due to the narrow screen width.
Assignment Problems Notice
Please do not email me to get solutions and/or answers to these problems. I will not give them out under any circumstances nor will I respond to any requests to do so. The intent of these problems is for instructors to use them for assignments and having solutions/answers easily available defeats that purpose.

Section 3-5 : Derivatives of Trig Functions

For problems 1 – 6 evaluate the given limit.

  1. \(\displaystyle \mathop {\lim }\limits_{t \to \,0} \frac{{3t}}{{\sin \left( t \right)}}\)
  2. \(\displaystyle \mathop {\lim }\limits_{w \to \,0} \frac{{\sin \left( {9w} \right)}}{{10w}}\)
  3. \(\displaystyle \mathop {\lim }\limits_{\theta \to \,0} \frac{{\sin \left( {2\theta } \right)}}{{\sin \left( {17\theta } \right)}}\)
  4. \(\displaystyle \mathop {\lim }\limits_{x \to \, - 4} \frac{{\sin \left( {x + 4} \right)}}{{3x + 12}}\)
  5. \(\displaystyle \mathop {\lim }\limits_{x \to \,0} \frac{{\cos \left( x \right) - 1}}{{9x}}\)
  6. \(\displaystyle \mathop {\lim }\limits_{z \to \,0} \frac{{\cos \left( {8z} \right) - 1}}{{2z}}\)

For problems 6 – 10 differentiate the given function.

  1. \(h\left( x \right) = {x^4} - 9\sin \left( x \right) + 2\tan \left( x \right)\)
  2. \(g\left( t \right) = 8\sec \left( t \right) + \cos \left( t \right) - 4\csc \left( t \right)\)
  3. \(y = 6\cot \left( w \right) - 8\cos \left( w \right) + 9\)
  4. \(f\left( x \right) = 8\sec \left( x \right)\csc \left( x \right)\)
  5. \(h\left( t \right) = 8 - {t^9}\tan \left( t \right)\)
  6. \(R\left( x \right) = 6\,\sqrt[5]{{{x^2}}} + 8x\sin \left( x \right)\)
  7. \(\displaystyle h\left( z \right) = 3z - \frac{{\cos \left( z \right)}}{{{z^3}}}\)
  8. \(\displaystyle Y\left( x \right) = \frac{{1 + \cos \left( x \right)}}{{1 - \sin \left( x \right)}}\)
  9. \(\displaystyle f\left( w \right) = 3w - \frac{{\sec \left( w \right)}}{{1 + 9\tan \left( w \right)}}\)
  10. \(\displaystyle g\left( t \right) = \frac{{t\cot \left( t \right)}}{{{t^2} + 1}}\)
  11. Find the tangent line to \(f\left( x \right) = 2\tan \left( x \right) - 4x\) at \(x = 0\).
  12. Find the tangent line to \(f\left( x \right) = x\sec \left( x \right)\) at \(x = 2\pi \).
  13. Find the tangent line to \(f\left( x \right) = \cos \left( x \right) + \sec \left( x \right)\) at \(x = \pi \).
  14. The position of an object is given by \(s\left( t \right) = 9\sin \left( t \right) + 2\cos \left( t \right) - 7\) determine all the points where the object is not changing.
  15. The position of an object is given by \(s\left( t \right) = 8t + 10\sin \left( t \right)\) determine where in the interval \(\left[ {0,12} \right]\) the object is moving to the right and moving to the left.
  16. Where in the range \(\left[ { - 6,6} \right]\) is the function \(f\left( z \right) = 3z - 8\cos \left( z \right)\) is increasing and decreasing.
  17. Where in the range \(\left[ { - 3,5} \right]\) is the function \(R\left( w \right) = 7\cos \left( w \right) - \sin \left( w \right) + 3\) is increasing and decreasing.
  18. Where in the range \(\left[ {0,10} \right]\) is the function \(h\left( t \right) = 9 - 15\sin \left( t \right)\) is increasing and decreasing.
  19. Using the definition of the derivative prove that \(\frac{d}{{dx}}\left( {\cos \left( x \right)} \right) = - \sin \left( x \right)\).
  20. Prove that \(\displaystyle \frac{d}{{dx}}\left( {\sec \left( x \right)} \right) = \sec \left( x \right)\tan \left( x \right)\).
  21. Prove that \(\displaystyle \frac{d}{{dx}}\left( {\cot \left( x \right)} \right) = - {\csc ^2}\left( x \right)\).
  22. Prove that \(\displaystyle \frac{d}{{dx}}\left( {\csc \left( x \right)} \right) = - \csc \left( x \right)\cot \left( x \right)\).